Penguatan Kelompok Sadar Wisata (Pokdarwis) Melalui Kampanye Sadar Wisata Untuk Menciptakan Pariwisata Berkelanjutan - Isma, Andika; Sumarsih, Sumarsih; Erwin, Erwin; Alisyahbana, Andi Naila Quin Azisah (Journal of Economic Education and Entrepreneurship Studies, 2023)
Some tourism village management by Pokdarwis has shortcomings in institutional function and effectiveness. These conditions directly affect the management and development of tourist villages. This community service activity aims to strengthen the institutional functions of Pokdarwis and other community institutions through the implementation of the 5.0 tourism awareness campaign launched by the Ministry of Tourism and Creative Economy. The community service program focuses on: (1) mentoring Pokdarwis; (2) mentoring PKK groups; (3) mentoring arts and cultural actors; and (4) mentoring youth organizations. Furthermore, this activity seeks to increase capacity, understanding and awareness among community groups in an effort to create sustainable tourism management. Evaluation through postest was carried out during the mentoring activities and after the mentoring activities as a form of evaluation. The evaluation results showed that 51 participants (85%) understood the importance of tourism awareness campaigns for institutional strengthening in creating sustainable tourism. The results of this community service are able to have a positive impact on sustainable tourism management. In addition, the results of this activity were able to equalize the positive perceptions of the community as stated in the memorandum of understanding.